High-Strength Hollow Glass Microsphere/Epoxy Resin Composite Insulation Materials for Deep In-Situ Condition Preserved Coring. (9th May 2022) - Yang, Jianping; Chen, Ling; He, Zhiqiang; Li, Cong; Yu, Bo; Wei, Zijie; Zhao, Zhiyu; Hao, Zongxin
Abstract : To establish in-situ fluidized coal mining technology and a theory of mining mechanics for deep coal resources, it is crucial to obtain a "fidelity rock core" that maintains deep in-situ conditions to understand the physical mechanics of deep rock. Doing so requires the development of in-situ condition-preserved coring (ICP-coring) technology. In this work, hollow glass microsphere/epoxy resin (HGM/EP) composite insulation materials with high strengths were prepared. An epoxy resin matrix with high strength and high-temperature resistance was selected from among epoxy resins cured by different curing agents. Then, a series of composite insulation materials with different HGM volume fractions were prepared. The mechanical strengths of the composites decreased with increasing HGM volume fraction. Then, thermal insulation materials suitable for different ICP-coring depths were selected. Changes in the thermal conductivities and mechanical strengths of the composites were characterized after they were subjected to high water pressure (45 MPa). Verification of the applicability of the thermal insulation material under high water pressure (45 MPa) conditions demonstrated that it met the working requirements for the ICP-coring device.